2018
DOI: 10.1590/1678-4162-9335
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of gastrointestinal parasites in Spheniscus magellanicus (Foster, 1781) located in Pontal do Sul, PR, Brazil

Abstract: Gastrointestinal parasitism is the main health problem faced by Spheniscus magellanicus, known as Magellanic penguins, in route on the Brazilian coast. The aim of this research was to report the occurrence and intensity of gastrointestinal parasites in S. magellanicus that reached Pontal do Sul, Paraná, South of Brazil. The study was performed at the Marine Study Center of the Federal University of Parana (CEM-UFPR) with 38 specimens, 31 were necropsied and seven were examined alive with coproparasitological e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Michels-Souza et al, 2010;Moura et al, 2018), contamination by petroleum (e.g. Barbieri, 2009;Michels-Souza et al, 2010), and impacts to animal health (Niemeyer, 2014;Ebert et al, 2016;Fink et al, 2018;Vanhoni et al, 2018;Martini et al, 2022). However, studies on the spatial distribution of seabirds along the Santos Basin are scarce, be they from at-sea counts or tracking data, and are restricted to few species and to the neritic region (< 20 m depth).…”
Section: Discussionmentioning
confidence: 99%
“…Michels-Souza et al, 2010;Moura et al, 2018), contamination by petroleum (e.g. Barbieri, 2009;Michels-Souza et al, 2010), and impacts to animal health (Niemeyer, 2014;Ebert et al, 2016;Fink et al, 2018;Vanhoni et al, 2018;Martini et al, 2022). However, studies on the spatial distribution of seabirds along the Santos Basin are scarce, be they from at-sea counts or tracking data, and are restricted to few species and to the neritic region (< 20 m depth).…”
Section: Discussionmentioning
confidence: 99%
“…There are currently 18 species of penguins registered, with the Magellanic penguin (Spheniscus magellanicus) being the most commonly found in temperate regions. They are found in the Falkland Islands and in regions of Argentina and Chile that comprise the Patagonian Desert, mainly during their breeding period between September and March (VANHONI et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Rio Grande do Sul have found 19500 carcasses in the coastal regions of the state in just one year, with 97% of them being young animals. These alarming data show that the population of Magellanic penguins has been drastically declining annually (VANHONI et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation